Clinical Significance of Polymorphisms in Immune Response Genes in Hepatitis C-Related Hepatocellular Carcinoma - De Re, Valli; Tornesello, Maria Lina; De Zorzi, Mariangela; Caggiari, Laura; Pezzuto, Francesca; Leone, Patrizia; Racanelli, Vito; Lauletta, Gianfranco; Gragnani, Laura; Buonadonna, Angela; Vaccher, Emanuela; Zignego, Anna Linda; et al. (Frontiers in Microbiology, 2019)
Background and Aims: Polymorphisms in the immune response genes can contribute to clearance of hepatitis C virus (HCV) infection but also mediate liver inflammation and cancer pathogenesis. This study aimed to investigate the association of polymorphisms in PD-1 (PDCD1), IFNL3 (IL28B), and TLR2 immune related genes in chronic HCV patients with different hepatic and lymphoproliferative HCV-related diseases. Methods: Selected PDCD1, IFNL3, and TLR2 genes were tested by molecular approaches in 450 HCV-positive patients with increasing severity of underlying liver diseases [including chronic infection (CHC), cirrhosis and hepatocellular carcinoma (HCC)], in 238 HCV-positive patients with lymphoproliferative diseases [such as cryoglobulinemia and non-Hodgkin lymphoma (NHL)] and in 94 blood donors (BD). Results: While the rs12979860 IFNL3 T allele was found a good marker associated with HCV-outcome together with the rs111200466 TLR2 del variant, the rs10204525 PD-1.6 A allele was found to have an insignificant role in patients with HCV-related hepatic disorders. Though in Asian patients the combination of IFNL3 and PD-1.6 markers better define the HCV-related outcomes, in our series of Caucasian patients the PD-1.6 A-allele variant was observed very rarely. Conclusion: Differences in the incidence of HCV-related HCC and clinical response between Asians and Europeans may be partially due to the distribution of PD-1.6 genotype that we found divergent between these two populations. On the other hand, we confirmed in this study that the polymorphic variants within IFNL3 and TLR2 immune response genes are significantly associated with HCV-related disease progression in our cohort of Italian patients.